Amebiasis in a Backyard Red-Foot Tortoise (Chelonoidis carbonaria) - Ferreira de Souto, Erick Platini; Moreira Campos, Édipo; Medeiros Miranda, Samuel Matheus; Medeiros Pereira, Kehrle Dantas; Sena Lima, Cinthia Dayanne; de Souza, Joyce Galvão; Nogueira de Galiza, Glauco José; Medeiros Dantas, Antônio Flávio (Acta Scientiae Veterinariae, 2020)
Background: Amebiasis is a parasitic infection caused by obligate or facultative amoeboid protozoans, as well as free-living forms. The genus Entamoeba includes both pathogenic and commensal species that can affect humans and animals. Entamoeba histolytica is the most important species associated with intestinal and extraintestinal infections in humans, while Entamoeba invadens is considered the most common and serious pathogen to many reptile species, including lizards, snakes and crocodilians. The aim of this manuscript is to report a case of amebiasis in a backyard red-foot tortoise in northeastern Brazil. Case: A 10-month-old male red-foot tortoise (Chelonoidis carbonaria) was presented at the Animal Pathology Laboratory of the Veterinary Hospital of Federal University of Campina Grande for necropsy with a 1-week history of anorexia, apathy, and reluctance to move. According to the owner, the animal suffered from heat stress in the backyard, where it was housed with another male red-foot tortoise. At post-mortem examination, there were approximately 1 mL of yellowish viscous transudate in the coelomic cavity. The liver was large, with rounded edges and multifocal to coalescing yellowish areas in the subcapsular surface. When cut, the parenchyma was more friable and yellowish. At the opening of the small intestine, the mucosa was thickened, reddened, and contained many variably sized, dark red ulcers with depressed and hemorrhagic centers. Histopathology of the liver reveals diffuse macro and microvacuolar degeneration of the hepatocyte cytoplasm, often displacing the nucleus peripherally (fatty degeneration). There were extensive and multifocal areas of necrosis characterized by shrunken, hypereosinophilic and pyknotic hepatocytes. Amebic trophozoites were seen through the areas of necrosis and degeneration and the morphological features were suggestive of the genus Entamoeba. In the portal triads and slightly extending to the sinusoidal spaces, there is a moderate inflammatory infiltrate of macrophages, lymphocytes, plasma cells and rare heterophils. There were amebic trophozoites and thrombi in hepatic vessels, and mild intracanalicular cholestasis. The small intestine contained areas of transmural necrosis and ulceration associated with inflammatory infiltrate of macrophages, lymphocytes and plasma cells. The ulcers were covered by a thick fibrinonecrotic exudate mixed with a varying number of heterophils and macrophages. The submucosa contained hemorrhage and edema. Similar amebic trophozoites were found within the mucosa and submucosa, and also detected in the lumens of blood vessels at the submucosa. The amebic trophozoites, seen in the liver and intestine, were intensely Periodic acid–Schiff positive. Discussion: The diagnosis of amebiasis was based on the epidemiological, clinical and anatomopathological findings. Amebiasis is a well-recognized disease that usually is diagnosed post-mortem in numerous species of reptiles. Unfortunately, there are no scientific articles describing these cases in Brazil. In reptiles, the major pathogenic specie is Entamoeba invadens, while several other species are considered non-pathogenic, such as E. barreti, E. insolita, E. terrapinae, E. ctenosaurae, and E. knowlesi, among others. Although cultivation of E. invadens was not undertaken, the anatomopathological findings and the morphological appearance of the agent is highly suggestive of infection with this organism. In conclusion, amebiasis is a severe infectious disease that can affect young red-footed tortoises under adverse environmental conditions. Clinical signs are nonspecific and may be difficult to identify. The diagnosis is usually made post-mortem by anatomopathological findings and the morphological appearance of the agent.